2009
DOI: 10.1111/j.1468-2478.2008.01522.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Negotiation: Some Experimental Findings from an International Negotiation Simulation1

Abstract: Increasingly, scholars have taken note of the tendency for women to conceptualize issues such as security, peace, war, and the use of military force in different ways than their male counterparts. These divergent conceptualizations in turn affect the way women interact with the world around them and make decisions. Moreover, research across a variety of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…In terms of gender-based differences in negotiating styles, Boyer et al (2009) found that statistically significant differences among middle school students became less marked among high school students. For example, all-female middle school groups had a much higher propensity to employ collaborative bargaining strategies than either male or mixed-gender groups.…”
Section: Research On Mun and Iconsmentioning
confidence: 94%
See 3 more Smart Citations
“…In terms of gender-based differences in negotiating styles, Boyer et al (2009) found that statistically significant differences among middle school students became less marked among high school students. For example, all-female middle school groups had a much higher propensity to employ collaborative bargaining strategies than either male or mixed-gender groups.…”
Section: Research On Mun and Iconsmentioning
confidence: 94%
“…Relatively little attention has been paid to studying the actual behavior of students in role-playing simulations, whether inside or outside of the classroom. Two exceptions to this trend are Rosenthal et al (2001) and the studies of Boyer and his colleagues on the ICONs project (Boyer et al 2009;Florea et al 2003). Rosenthal et al (2001) conducted a study of the 1999 Model United Nations of the Southwest, sponsored by the University of Oklahoma and attracting high school students from Texas, New Mexico, and Oklahoma.…”
Section: Research On Mun and Iconsmentioning
confidence: 94%
See 2 more Smart Citations
“…Several classifications of tactics have been proposed. Prominently among them are value-claiming versus value-creating (Lax and Sebenius 1986); distributive versus integrative bargaining (Walton and McKersie 1965); bargaining versus problem-solving (Hopmann 1995); strategic action versus communicative action (Niemann 2004); problem-solving, contending, yielding and inaction (Pruitt 1983); bargaining versus arguing (Risse 2000); collaborative, conflictual, reciprocal, self-interested, assertive and creative negotiating (Boyer et al 2009); and hard versus soft bargaining (Dür and Mateo 2010;Hopmann 1974). All of these classifications are based on ideal types; in fact, all of the above scholars recognize that negotiators often mix tactics that belong to different ideal-typical categories that they propose.…”
Section: Classifying Negotiation Tacticsmentioning
confidence: 99%